Structure-centered portal for child psychiatry research - Rane, Pallavi; Haselgrove, Christian; Hodge, Steven M.; Frazier, Jean A.; Kennedy, David N. (Frontiers in Neuroinformatics, 2014)
The real world needs of the clinical community require a domain-specific solution to integrate disparate information available from various web-based resources for data, materials, and tools into routine clinical and clinical research setting. We present a child-psychiatry oriented portal as an effort to deliver a knowledge environment wrapper that provides organization and integration of multiple information and data sources. Organized semantically by resource context, the portal groups information sources by context type, and permits the user to interactively 'narrow' or 'broaden' the scope of the information resources that are available and relevant to the specific context. The overall objective of the portal is to bring information from multiple complex resources into a simple single uniform framework and present it to the user in a single window format.